Modelo de Van Hiele en el aprendizaje de cuadriláteros, en estudiantes del cuarto grado de educación secundaria, Huancavelica - Huamán Arotoma, Armando (2024)
This research is the result of a thesis and comprises a study on the implementation of the Van Hiele model in the learning of quadrilaterals among fourth-grade secondary education students in a rural area of Huancavelica. The research was an explanatory level, with a pre-experimental design involving a single group of 12 students, who formed both the population and the sample. A pre-test was administered to the students, followed by a set of eight activities containing geometry materials focused on quadrilaterals, designed using the Van Hiele model. The development of the activities or class sessions took place over two months. After completing the class sessions, a post-test was administered as a pedagogical assessment. The results from the post-test indicated that the students' level of learning was higher compared to the beginning of the academic activities. Additionally, the students reached Van Hiele Level 4 in their understanding of the concept of quadrilaterals, in contrast to the pre-test results, where some students were at level 0. This evidence shows that the Van Hiele model significantly contributed to the students' deeper understanding of the topic of quadrilaterals.